An Experimental Study on the Mechanical Characteristics of Natural and Synthetic Fiber-Reinforced Sandy Soil in Pavement Construction - Mahdi Ghasemi Nezhad; Alireza Tabarsa (Journal of Natural Fibers, 2023)
The current study investigated the use of polyester synthetic (PES) fiber and basalt (BS) and bagasse (BG) natural fibers on the strength and mechanical behavior of sandy soil in pavement construction projects. A series of California bearing ratio (CBR) and indirect tensile strength (ITS) tests were performed on fiber contents (FC) of 0.5,1 and 2% and fiber lengths (FL) of 2.5, 5, and 7.5 mm. Findings show that the maximum California bearing ratio (by increasing 3.3 times) and indirect tensile strength (by increasing 2.98 times) are obtained in the length of 7.5 mm and the content of 2% for polyester and basalt fibers, respectively, which is also evident in the scanning electron microscope (SEM) test results. Also, based on the analysis of variance (ANOVA) and according to various factors including P-value (<0.05), it was determined that the contrast between the values is statistically significant. Due to California bearing ratio – indirect tensile strength and California bearing ratio – resilient modulus experimental relationships, the relationship between resilient modulus-indirect tensile strength was provided with very good correlation coefficients. Furthermore, sensitivity analysis revealed that California bearing ratio and indirect tensile strength values are noticeably influenced by fiber content variations.